Host immune responses after hypoxic reactivation of IFN-γ induced persistent Chlamydia trachomatis infection - Jerchel, Stefan; Kaufhold, Inga; Schuchardt, Larissa; Shima, Kensuke; Rupp, Jan (Frontiers in Cellular and Infection Microbiology, 2014)
Genital tract infections with Chlamydia trachomatis (C. trachomatis) are the most frequent sexually transmitted disease worldwide. Severe clinical sequelae such as pelvic inflammatory disease (PID), tubal occlusion and tubal infertility are linked to chronic inflammatory processes of persistently infected tissues. The oxygen concentrations in the female urogenital tract are physiologically low and further diminished (0.5-5 % O2, hypoxia) during an ongoing inflammation. However, little is known about the effect of a low oxygen environment on genital C. trachomatis infections. In this study, we investigated the host immune responses during reactivation of IFN-γ induced persistent C. trachomatis infection under hypoxia. For this purpose, the activation of the MAP-kinases p44/42 and p38 as well as the induction of the pro-inflammatory cytokines IL-1β, IL-6, IL-8 and MCP-1 were analyzed. Upon hypoxic reactivation of IFN-γ induced persistent C. trachomatis infection, the phosphorylation of the p44/42 but not of the p38 MAP-kinase was significantly diminished compared to IFN-γ induced chlamydial persistence under normoxic condition. In addition, significantly reduced IL-6 and IL-8 mRNA expression levels were observed for reactivated Chlamydiae under hypoxia compared to a persistent chlamydial infection under normoxia. Our findings indicate that hypoxia not only reactivates IFN-γ induced persistent C. trachomatis infections resulting in increased bacterial growth and progeny but also dampens inflammatory host immune signaling responses that are normally observed in a normoxic environment.